VD_FINDINFO AP / 2012 / 22 vom 2. September 2010 - VD Tribunal cantonal (2010)
LOYER ABUSIF, BAIL À LOYER, FARDEAU DE LA PREUVE, PREUVE, LOYER INITIAL | 8 CC, 253a al. 1 CO, 269 CO, 269a let. a CO, 270 CO, 444 CPC, 445 CPC, 451 ch. 2 CPC, 452 al. 1 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 465 al. 3 CPC, 466 al. 1 CPC, 13 LTB, 405 al. 1 CPC (CH)